Adaptation of Students Depending on the Type of Temperament to Educational Activities in Higher School in the Conditions of Online Learning - Kashina, Julia V.; Gluzman, Iuliya V.; Oparina, Nina A.; Gribkova, Galina I.; Ershova, Olga V.; Umerkaeva, Sofiya Sh. (International Journal of Criminology and Sociology, 2022)
The article examines the influence of the type of temperament on the adaptation of students to educational activities at the university in the context of online learning. The article's main aim is to study the regulatory-adaptive status of students depending on the classical and mixed types of temperament. To do so, we analyze and investigate a number of sources on this issue. For the successful adaptation of students to educational activities in the context of online learning, higher school teachers should determine what properties and characteristics of the nervous system their students have. The authors conclude that the regulatory-adaptive abilities of students to the educational process depend on the type of temperament. They are the highest among phlegmatic/sanguine students and the lowest among melancholic students.